Bacterial colonization on coated and uncoated orthodontic wires: A prospective clinical trial - Seyed Hamid Raji; Hasan Shojaei; Parinaz Saeidi Ghorani; Elahe Rafiei (Wolters Kluwer Medknow Publications, 2014)
Background: The advantages of coated orthodontic wires such as esthetic and their effects on reduced friction, corrosion and allergic reaction and the significant consequences of plaque accumulation on oral health encouraged us to assess bacterial colonization on these wires. Materials and Methods: A total of 18 (9 upper and 9 lower) epoxy resin coated 16 × 22 nickel-titanium wires (Spectra, GAC, USA) and 18 (9 upper and 9 lower) non-coated 16 × 22 nickel-titanium wires (Sentalloy, GAC, USA) with isolated packages were selected and sterilized before application. The samples were divided randomly between upper and lower arches in 18 patients and hence that every patient received one coated and one uncoated wire at the same time. Samples were removed and cut in equal lengths after 3 weeks and placed in phosphate buffered saline buffer. After separation of bacteria in trypsin and ethylenediaminetetraacetic acid solution, the diluted solution was cultured in blood agar and bacterial colony forming units were counted. Finally, the data was analyzed using the paired t-test and the significance was set at 0.05. Results: Mean of bacterial colonization on uncoated wires was more than that of coated wires (P < 0.001). Conclusion: Bacterial plaque accumulation on epoxy resin coated nickel-titanium orthodontic wires is significantly lower than uncoated nickel-titanium wires.